2011
DOI: 10.1007/s00775-011-0754-2
|View full text |Cite
|
Sign up to set email alerts
|

Chemical reactivity of Synechococcus sp. PCC 7002 and Synechocystis sp. PCC 6803 hemoglobins: covalent heme attachment and bishistidine coordination

Abstract: In the absence of an exogenous ligand, the hemoglobins from the cyanobacteria Synechocystis sp. PCC 6803 and Synechococcus sp. PCC 7002 coordinate the heme group with two axial histidines (His46 and His70). These globins also form a covalent linkage between the heme 2-vinyl substituent and His117. The in vitro mechanism of heme attachment to His117 was examined with a combination of site-directed mutagenesis, NMR spectroscopy, and optical spectroscopy. The results supported an electrophilic addition with vinyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
65
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(68 citation statements)
references
References 77 publications
3
65
0
Order By: Relevance
“…As a rapid test for heme modifications, the hemochromogen assay 25 was performed as previously reported. 20 DT-reacted samples were typically reduced for 1−2 h to allow for complete conversion prior to the samples being assayed. The results were interpreted by comparison with published spectra (α and β band maxima).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…As a rapid test for heme modifications, the hemochromogen assay 25 was performed as previously reported. 20 DT-reacted samples were typically reduced for 1−2 h to allow for complete conversion prior to the samples being assayed. The results were interpreted by comparison with published spectra (α and β band maxima).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…6B), respectively, as well as NMR structure for PCC 7002 (PDB ID: 2KSC [67]). The combination of site-directed mutagenesis, NMR and optical spectroscopic studies provided evidence that the His-heme cross-link in reduced cyanobacteria Hbs was formed by an electrophilic addition with a reduction-driven mechanism (Scheme 4) [68]. Moreover, the His-heme cross-link was found to be self-amplified with the intrinsic ability of cyanobacteria Hbs to perform interprotein electron exchange [69].…”
Section: C-n Bondmentioning
confidence: 99%
“…Moreover, the His-heme cross-link was found to be self-amplified with the intrinsic ability of cyanobacteria Hbs to perform interprotein electron exchange [69]. It was shown that introduction of a cysteine at position 117 (H117C mutation) of PCC 6803 can result in formation of a thioether bond with the heme 2-vinyl group [68], suggesting that this position is suitable for both His-heme and Cys-heme cross-links. Despite the fact, cyanobacteria Hbs prefer the His-heme cross-link, likely due to its advantages such as less interference under high oxidative and nitrosative stress conditions that many cyanobacteria encounter [67].…”
Section: C-n Bondmentioning
confidence: 99%
See 2 more Smart Citations